PROSES PEMBERDAYAAN EKONOMI KELUARGA MELALUI PROGRAM UMKM KERIPIK CIRENG RASAKU DI DESA CIBATU KECAMATAN CISAAT KABUPATEN SUKABUMI - Ali Munajib; Muhtadi Muhtadi (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2022)
The Covid-19 pandemic has caused many people to lose their jobs, this has an impact on increasing the number of unemployment and poverty in Indonesia, and can make the national economy experienced a crisis. The Family Welfare Empowerment Group should contribute to building the national economy by optimizing the family economy through Micro, Small, and Medium Enterprises (MSMEs) in the community.The method used in this research is qualitative research with a descriptive research type. Data collection techniques were carried out using interviews, observations, and documentation studies. The resource persons in this study were 8 members of the Cireng Rasaku Chips MSMEs. The results of this study are the process of empowering the family economy at the Cireng Rasaku Chips MSMEs. including the awareness process, the knowledge transfer process, and the enrichment process. Then, in this study, only three of the four indicators of empowerment were achieved, namely freedom of mobility, the ability to buy small commodities as well as economic security, and contribution to the family. The driving factor in this empowerment is the existence of a partnership program and adequate quality of human resources. The inhibiting factors include limited capital, limited marketing capabilities, limited access to business information, and selfish between members.